Gas-saturated solution process to obtain microcomposite particles of alpha lipoic acid/hydrogenated colza oil in supercritical carbon dioxide. (17th August 2016) - Mishima, Kenji; Honjo, Masatoshi; Sharmin, Tanjina; Ito, Shota; Kawakami, Ryo; Kato, Takafumi; Misumi, Makoto; Suetsugu, Tadashi; Orii, Hideaki; Kawano, Hiroyuki; Irie, Keiichi; Sano, Kazunori; et al.
Abstract: Alpha lipoic acid (ALA), an active substance in anti-aging products and dietary supplements, need to be masked with an edible polymer to obscure its unpleasant taste. However, the high viscosity of the ALA molecules prevents them from forming microcomposites with masking materials even in supercritical carbon dioxide (scCO2 ). Therefore, the purpose of this study was to investigate and develop a novel production method for microcomposite particles for ALA in hydrogenated colza oil (HCO). Microcomposite particles of ALA/HCO were prepared by using a novel gas-saturated solution (PGSS) process in which the solid-dispersion method is used along with stepwise temperature control (PGSS-STC). Its high viscosity prevents the formation of microcomposites in the conventional PGSS process even under strong agitation. Here, we disperse the solid particles of ALA and HCO in scCO2 at low temperatures and change the temperature stepwise in order to mix the melted ALA and HCO in scCO2 . As a result, a homogeneous dispersion of the droplets of ALA in melted HCO saturated with CO2 is obtained at high temperatures. After the rapid expansion of the saturated solution through a nozzle, microcomposite particles of ALA/HCO several micrometers in diameter are obtained.